Alkaline earth complexes of a sterically demanding guanidinate ligand - Moxey, Graeme J.; Blake, Alexander J.; Lewis, William; Kays, Deborah L. (Wiley, 2015)
The synthesis of the guanidine MesN{C(NCy2)}N(H)Mes (LH; Mes = 2,4,6-Me3C6H2, Cy = cyclohexyl), and its use as a proligand for the synthesis of alkaline earth metal complexes are reported. Described herein are (i) an unusual Hauser base cubane, (ii) a homoleptic and a base-stabilized magnesium complex featuring the same guanidinate ligands, and (iii) the comparison of a series of alkaline earth (Mg, Ca, Sr, Ba) bis(guanidinate) complexes, which allows the opportunity to compare the changing trends in bonding as the Group is descended. The reaction between LH and MeMgI(OEt2)2 yields the Hauser base as a mixture of the tetramer [Mg4L4(μ3-I)4] (1a) and dimer [Mg2L2(μ-I)2(OEt2)2] (1b), and the reaction with two equivalents of MgnBu2 leads to the formation of four-coordinate [MgL2] (2), which features a square-planar geometry for the magnesium cation, or five-coordinate [MgL2(THF)] (3), depending on the solvent used. 1a is the first crystallographically-characterized cubane structure to consist of four LAeX (L = ligand, X = halide) units. The complexes [AeL2(THF)2] (Ae = Ca, 4; Ae = Sr, 5) and [BaL2] (6) were synthesized via redox transmetallation/ligand exchange reactions. Complex 6 is the first example of a homoleptic, monomeric barium complex of the NCN ligand family, with the structure stabilized by a number of barium-arene interactions in the solid state.